Otaku and the Struggle for Imagination in Japan - Galbraith, Patrick W. (Book collections on Project MUSE., 2019)
"In this ethnographic study of Otaku-- a loose category referring to intense fans of Japanese animation, games, and comics-- conducted in Akihabara, the electronics-turned-pop-culture neighborhood of Tokyo, author Patrick Galbraith traces the evolving relationships of mostly male-fans with imagined female characters. The term otaku, he argues, is frequently pathologized, to mean alienated or introverted persons - usually male - who have difficulty having real relationships and thus retreat into a world of their own imagination and control. Galbraith wonders why the form of a relationship that focuses on an animated character is more problematic than other kinds of fan attachments - crushes on pop music stars or a deep investment in Star Wars or Harry Potter. Through his engaged ethnography at the height of the interest in maid cafes and animated female characters in the early 2000s, he is able to historicize this fandom in an empathetic and detailed way, showing that what many have taken to be a single and peculiar psychological phenomenon was actually a complex, quickly evolving pop culture phenomenon. The affective relationships of the fans (seen as 3D) and the characters (2D, even when they are in three dimensions) is seen as a shifting and ordered form of closeness, a closeness between humans and animated characters. Galbraith urges us to explore rather than denigrate these relationships."--